2021
DOI: 10.1039/d1cc01228b
|View full text |Cite
|
Sign up to set email alerts
|

A near-infrared fluorescent probe for accurately diagnosing cancer by sequential detection of cysteine and H+

Abstract: A near-infrared fluorescence probe CyAc is synthesized for accurately diagnosing cancer in vivo by sequential detection of Cys and H+. CyAc can not only achieve a good distinction of normal...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…16,31 Consequently, monitoring fluctuations in Cys levels of live cells via imaging based approaches is extremely desirable for studying the pathophysiology of these diseases and can also facilitate their early diagnosis and treatment. 45–49,65,66 Motivated by these desirable applications of live cell Cys imaging, we employed our MADELCY TOF probes for imaging Cys in live HeLa mammalian cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…16,31 Consequently, monitoring fluctuations in Cys levels of live cells via imaging based approaches is extremely desirable for studying the pathophysiology of these diseases and can also facilitate their early diagnosis and treatment. 45–49,65,66 Motivated by these desirable applications of live cell Cys imaging, we employed our MADELCY TOF probes for imaging Cys in live HeLa mammalian cells.…”
Section: Resultsmentioning
confidence: 99%
“…The 1,2-aminothiol moiety is a unique structural feature of free Cys and provides opportunities to design Cys-selective fluorescent probes that are insensitive towards other amino acids and biothiols. 42,43 Indeed, several 1,2-aminothiol-derivatization reactions have been previously employed for developing fluorescence-based Cys detection probes including Michael addition–cyclization reactions, 44–48 S N Ar substitution–rearrangement, 49–53 and cyclization reactions with aldehydes. 54–57 A major limitation of several of these reactions is that they proceed in sub-optimal yields and demonstrate slow reaction kinetics, hampering probe sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas biomarkeractivatable probes only generate fluorescent signals when they come across the specific biomarker, that's why imaging with biomarker-activatable probes can achieve much higher sensitivity with inappreciable background noise. [44][45][46][47][48][49][50][51][52][53] Therefore, a biomarker-activatable probe with NIR-II fluorescent imaging would provide a utilitarian means for accurate detection of H 2 O 2 in-vivo in the plant sprouts and the ensuing warning of heavy-metal ion or high-level salt pollution in soil/water.…”
Section: Introductionmentioning
confidence: 99%
“…Fluorescent probes are commonly used as an efficient approach for the in situ and real-time detection of various analytes in biological systems due to their advantages such as fast and sensitive response, good selectivity, water solubility, and low cytotoxicity. In particular, near-infrared (NIR) fluorescent probes have longer absorption and emission wavelengths, penetrating deep tissues to reduce the background fluorescence, which has attracted much attention. Up to now, some H 2 S NIR fluorescent probes have been developed. For example, Zhang et al reported a H 2 S NIR fluorescent probe successfully applied in tumor imaging . Unfortunately, the signal interference caused by some normal organs such as the liver and kidney could not be ruled out.…”
Section: Introductionmentioning
confidence: 99%